RENDEMEN EKSTRAK ETANOL DAN UJI FITOKIMIA TIGA JENIS TUMBUHAN OBAT KALIMANTAN BARAT (Rendement of Ethanol Extracts and Phytochemical Tests In Three of Species Medicinal Plants of West Borneo) - Yusro, Fathul (jurnal TENGKAWANG, 2011)
The tropical rain forest in West Borneo has a variety of plants species that have been used as an ingredient in traditional medicines such as pelanjau wood (Pentaspadon motleyi Hook.f), bakau wood (Rhizopora apiculata) and gerunggang bark (Cratoxylum arborescens (Vahl) Bl). Aim of this research is to determine the yields of pelanjau wood, bakau wood and gerunggang bark ethanol-soluble extracts and bioactive compounds through phytochemical tests. The extraction using was done ethanol as solvent and by maceration. The extracts of obtained phytochemical tested. The results showed that the yield of ethanol extracts pelanjau wood, bakau wood and gerunggang bark was 7,14%; 4,34% and 9,47%, respectively. Pelanjau wood extracts contained the bioactive compounds tannins and flavonoids; bakau wood and gerunggang bark contained tannins, saponins, flavonoids and quinines Key word : Rendement, ethanol extracts, phytochemical, medicinal plant, West Borneo